Brisk heart rate and EEG changes during execution and withholding of cue-paced foot motor imagery - Pfurtscheller, Gert; Solis Escalante, Teodoro; Barry, Robert J.; Klobassa, Daniela S.; Neuper, Christa; Mueller-Putz, Gernot (Frontiers in Human Neuroscience, 2013)
Cue-paced motor imagery is a frequently used mental strategy to realize a Brain-Computer Interace (BCI). Recently it has been reported that 2 motor imagery tasks can be separated with a high accuracy within the first second after cue presentation onset. To investigate this phenomenon in detail we studied the dynamics of motor cortex beta oscillations in EEG and the changes in heart rate (HR) during visual cue-paced foot imagery using a go (execution of imagery) versus nogo (withholding of imagery) paradigm in 16 healthy subjects. Both execution and withholding of motor imagery resulted in a brisk centrally localized beta ERD with a maximum at ~ 400 ms and a concomitant HR deceleration. We found that response patterns within the first second after stimulation differed between conditions. The ERD was significantly larger in go as compared to nogo. In contrast the HR deceleration was somewhat smaller and followed by an acceleration in go as compared to nogo. These findings suggest that the early beta ERD reflects visually induced preparatory activity in motor cortex networks. Both the early beta ERD and HR deceleration are the result of automatic operating processes that are likely part of the orienting reflex. Of interest, however, is that the preparatory cortical activity is strengthened and the HR modulated already within the first second after stimulation during the execution of motor imagery. The subtraction of the HR time course of the nogo from the go condition revealed a slight HR acceleration in the first seconds most likely due to the increased mental effort associated with the imagery process.